Public Administration Innovation in Supporting the Digital Tourism Ecosystem - Arimbawa, I Gede Arya Pering; Muhammad, A Fadel (Program Pascasarjana Universitas Negeri Makassar, 2024)
Digital tourism has changed the paradigm of the tourism industry by utilizing information and communication technology (ICT) to improve interactions between tourist destinations and visitors. This research highlights the important role of innovation in public administration in building an inclusive and sustainable digital tourism ecosystem. Through descriptive analysis and literature review, this research reveals that the use of mobile applications, digital platforms, and big data has changed the way tourism destinations are managed. The government's implementation of ICT improves the efficiency of public services, expands information accessibility for tourists, and supports environmental conservation efforts. Case studies from various countries show that the adaptation of technology in public administration not only improves operational efficiency but also promotes active participation in sustainable tourism activities. Despite its positive potential, the implementation of digital tourism is faced with a number of challenges. Low digital literacy among tourism industry players and personal data protection issues are the main barriers to adopting new technologies. Strong collaborative efforts between the government, private sector, and the community are important to create a dynamic and adaptive tourism ecosystem. Data integration between various stakeholders is expected to improve coordination and effectiveness in decision-making, as well as promote sustainable innovation in tourism management. This research underscores that innovation in public administration is not only about the application of technology, but also about broader transformations in the way government interacts with society and industry. By understanding the impact of technology on public administration and the development of digital tourism ecosystems, this research provides a foundation for the development of responsive and effective public policies in the face of the digital age and globalization in the tourism sector.